Treatment experience of coronavirus infection associated with SARS-CoV-2 in patients with acute myeloid leukemia in the older age group - L. T. Shimanovskaya; E. N. Misyurina; E. A. Baryakh; E. I. Zhelnova; K. V. Yatskov; T. S. Chudnova; A. B. Makeshova; M. A. Mingalimov; D. D. Ivanova; O. L. Kochneva; E. N. Zotina; T. N. Tolstykh; et al. (Онкогематология)
Aim. To study the course of COVID-19 (COronaVIrus Disease 2019) in elderly patients with acute myeloid leukemia (AML), to analyze risk factors for unfavorable outcome.Materials and methods. The paper presents our own experience in the treatment of elderly (age ≥65 years) patients with AML and concomitant coronavirus infection in the hematology departments of City Clinical Hospital No. 52 (Moscow) from March 2020 to June 2022. The diagnosis of COVID-19 was considered confirmed based on a positive result of the polymerase chain reaction of an oropharyngeal and nasopharyngeal swab for SARS-CoV-2 and/or a typical radiological picture on a computed tomogram of the lungs.Results. An analysis of clinical, laboratory and instrumental data of 59 patients (30 (51 %) men, 29 (49 %) women) with AML and COVID-19 was carried out. All patients were treated for COVID-19 in accordance with the Temporary guidelines “Prevention, diagnosis and treatment of new coronavirus infection (COVID-19)” of the Russian Ministry of Health. Median age was 71 (65-91) years. AML was first verified in 27 % of hospitalized patients; 12 % were in remission of the disease. A month before hospitalization, 36 % of patients received antitumor therapy, and 19 % of patients had refractory AML. 17 % of hospitalized patients received antitumor therapy with cytarabine in small doses for vital indications. Death was recorded in 64 % of cases, in 24 % the cause of death was severe COVID-19. The unfavorable outcome was influenced by addition of secondary bacterial flora, refractory AML course and elderly age of patients.Conclusion. Pre-exposure prophylaxis with monoclonal antibodies and vaccination of patients may be the main methods of preventing infection and severe course of COVID-19.